Um conjunto de esporas medievais provenientes do Convento de S. Salvador de Vilar de Frades (Barcelos) - Erasun Cortés, Ricardo; Faure, Francisco Líbano Monteiro (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
Four medieval spurs are described in the present paper. These spurs were found at the Monastery of Vilar de Frades (Barcelos) excavations during 1999 and are presumably from the 13th-15th centuries.